Best practices for time‐resolved serial synchrotron crystallography. Issue 1 (23rd December 2021) - Schulz, Eike C.; Yorke, Briony A.; Pearson, Arwen R.; Mehrabi, Pedram
Abstract : The key factors that should be considered during the planning and execution of a time‐resolved crystallographic experiment are discussed, with a focus on time‐resolved serial synchrotron crystallography. Abstract : With recent developments in X‐ray sources, instrumentation and data‐analysis tools, time‐resolved crystallographic experiments, which were originally the preserve of a few expert groups, are becoming simpler and can be carried out at more radiation sources, and are thus increasingly accessible to a growing user base. However, these experiments are just that: discrete experiments, not just `data collections'. As such, careful planning and consideration of potential pitfalls is required to enable a successful experiment. Here, some of the key factors that should be considered during the planning and execution of a time‐resolved structural study are outlined, with a particular focus on synchrotron‐based experiments.